Lake variables - Sonde profiling from Bolmen, Subbasin South, 2022-07-12–2025-11-03 - Bolmen Research Station (Swedish University of Agricultural Sciences, 2026)
Manual or high frequency lake profiling using sonde technology over various water depths to measure lakes of SITES Water.
Bolmen Research Station (2026). Lake variables - Sonde profiling from Bolmen, Subbasin South, 2022-07-12–2025-11-03 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/IYgCNorDyd7Q_2qE5vdIynrl
Keywords: Bolmen Research Station; Chlorophyll concentration; Conductivity; Lake; Turbidity; Time instant; Time instant; Water temperature; Water temperature; Electrical conductivity; Electrical conductivity; Specific conductivity; Specific conductivity; pH; pH; Oxidation Reduction Potential; Oxidation Reduction Potential; Turbidity_FNU; Turbidity_FNU; Chlorophyll fluorescence; Chlorophyll fluorescence; Oxygen saturation; Oxygen saturation; Fluorescent dissolved organic matter; Fluorescent dissolved organic matter; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap